Hypernuclear weak decay puzzle - Barbero, César Alberto (2002)
A general shell model formalism for the nonmesonic weak decay of the hypernuclei has been developed. It involves a partial wave expansion of the emitted nucleon waves, preserves naturally the antisymmetrization between the escaping particles and the residual core, and contains as a particular case the weak Λ-core coupling formalism. The extreme particle-hole model and the quasiparticle Tamm-Dancoff approximation are explicitly worked out. It is shown that the nuclear structure manifests itself basically through the Pauli principle, and a very simple expression is derived for the neutron- and proton-induced decays rates Γn and Γp, which does not involve the spectroscopic factors. We use the standard strangeness-changing weak ΛN→NN transition potential which comprises the exchange of the complete pseudoscalar and vector meson octets (π,η,K,ρ,ω,K*), taking into account some important parity-violating transition operators that are systematically omitted in the literature. The interplay between different mesons in the decay of ¹²ΛC is carefully analyzed. With the commonly used parametrization in the one-meson-exchange model (OMEM), the calculated rate ΓNM = Γn + Γp is of the order of the free Λ decay rate Γ⁰(ΓthNM ≅ Γ⁰) and is consistent with experiments. Yet the measurements of Γn/p = Γn / Γp and of Γp are not well accounted for by the theory (Γthn/p ≲ 0.42,Γthp ≳ 0.60Γ⁰). It is suggested that, unless additional degrees of freedom are incorporated, the OMEM parameters should be radically modified.